The debate on staff language competences and the use of official languages in the Balearic Islands health system - Ballester Cardell, Maria; Marí Mayans, Isidor (Linguistic Minorities and Society, 2021)
The Spanish Constitution of 1978 and the Statute of Autonomy of the Balearic Islands of 1983 established the official nature of both Spanish and Catalan and entrusted public authorities with guaranteeing the right of citizens to use one or the other on an equal footing. Subsequent to the language legislation of 1986, the legal framework of Catalan has varied depending on the majority party that forms a government. The debate stirred up by these regulations demonstrates the difficulties in ensuring real equality between official languages, when social initiatives cannot translate into sufficient political support and the national political context is hostile. The article explores this debate and discusses recent regulations surrounding the official languages competencies of health system staff, from the direct experience of the authors, as members of two consultative institutions on legal and sociolinguistic matters. Keywords: language rights, official language, language competence, medical communication, health services

Santé et mieux-être des élèves francophones au Nouveau-Brunswick (Canada) - Boivin, Nathalie; Foulem, Ghislaine; Desjardins, Isabelle Perron (La Revue de Santé Scolaire et Universitaire, 2025)

Public policy and citizen-based practices that support social and health services for official and co-official language minority communities. An international perspective: What has really been achieved and what are the gaps | Politiques publiques et pratiques citoyennes soutenant les services sociaux et de santé pour les communautés minoritaires de langue officielle et coofficielles. Une perspective internationale : ce qui a été accompli et ce qui reste à faire - Bouchard, Louise; Nyqvist, Fredrica; Mari Mayans, Isidor; van Kemenade, Solange; Maisonneuve, Alexander. R. (Linguistic Minorities and Society / Minorités linguistiques et société, 2021)

Le moment Monfort dans la francophonie canadienne. - Charbonneau, François (Presses de l’Université d’Ottawa, 2024)

The principle of minority protection and language rights in Canada: The secession reference’s legacy - Chouinard, Stéphanie (Journal of Parliamentary and Political Law, 2021)

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

Une question de respect et de sécurité : l’incidence des situations d’urgence sur les langues officielles - Commissariat aux langues officielles (Gouvernement du Canada, 2020)

Vers une amélioration de la prestation de services de santé pour les Franco-Ontariens - Doucet, Pascale-Anne. M.; Gorham, Robyn; Hunt, Elena (Journal de recherche interdisciplinaire, 2021)
Malgré le statut de dualité linguistique du Canada, la communauté francophone continue d’être laissée pour compte par les autorités du pays. Plus spécifiquement, l’étendue et l’accès restreints des services de santé offerts aux francophones en Ontario posent un grave danger pour cette population. Les établissements qui dispensent des services de santé continuent d’ignorer les politiques de soins existantes. Cette situation impose plusieurs actions au niveau fédéral, législatif et communautaire nécessaires afin d’assurer la garantie bilingue promise à la population canadienne. Parmi celles-ci, il faut augmenter la présence francophone dans les groupes décisionnels pour assurer la conception et l’établissement de programmes et services de santé axés sur les besoins uniques et distincts des franco-ontariens. Par ailleurs, l’engagement financier fédéral envers des organismes communautaires francophones est essentiel afin de fournir plus de services de santé en français, surtout dans les communautés nordiques et rurales de la province. Finalement, la subvention gouvernementale de futures recherches sur la santé des francophones est nécessaire puisque celles-ci vont servir de base solide pour déterminer comment mieux desservir cette population. Pour y arriver, il faudrait considérer le lobbying, l’encouragement des institutions qui dispensent des services de santé d’obtenir leur désignation bilingue, et la mise à jour de la Loi sur les services en français. Cependant, en continuant l’inaction, les Franco-Ontariens risquent de devenir assimilés au restant de la population, de dépérir et de voir leur santé se détériorer. Cet article cherche notamment à signaler la nécessité d’améliorer la prestation de services de santé en français en Ontario.

mobilisation collective pour une santé en français en ontario. closm santé - Forest, Mariève; Gilbert, A.; Bouchard, Louise (Le moment Monfort dans la francophonie canadienne, 2024)

50 ans de législation en matière de langues officielles au Canada : bilan et perspectives - Forgues, Éric; Donovan, Patrick; Labelle Eastaugh, Érik; O’Donnell, Lorraine (Minorités linguistiques et société, 2021)

50 Years of Legislation Concerning Official Languages in Canada: Review and Prospects - Forgues, Éric; Donovan, Patrick; Labelle Eastaugh, Érik; O’Donnell, Lorraine (Minorités linguistiques et société, 2021)

L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

L'effectivité des lois linguistiques dans le secteur de la santé. Rapport - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Sommaire - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

Populations de langue officielle en situation minoritaire selon différentes méthodes de dénombrement. Rapport - Guignard Noël, Josée; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2020)

Language-based welfare services in times of structural change: An examination of Finland’s social and healthcare reform (2023) - Himmelroos, Staffan; Sjöblom, Stefan; Vento, Isak (Revista de Llengua i Dret, 2025)
This study examines the impact of Finland’s social and healthcare reform on language-based welfare services for the Swedish-speaking population of Finland. The reform shifted healthcare responsibility from municipalities to regional wellbeing service counties (WBSCs), altering established linguistic boundaries in the process. Traditionally, municipalities have ensured the provision of services in both Finnish and Swedish in bilingual areas. Post-reform, Swedish speakers that represent a majority or substantial minority within a municipality have become a small minority within larger WBSCs, some of which include unilingual areas that lack experience in providing bilingual services. Analysis of survey data indicates that Swedish speakers in majority Swedish-speaking municipalities are the most satisfied with language services, while those in minority areas are significantly less satisfied. Notwithstanding, satisfaction among Swedish speakers in majority areas has declined significantly since the reform. The study highlights the challenges of maintaining language rights within a universal healthcare system amid structural changes and emphasises the importance of addressing linguistic needs in a state with two national languages. , Aquest estudi analitza l’impacte de la reforma social i sanitària en els serveis socials i de salut basats en la llengua per a la població de parla sueca de Finlàndia. La reforma va traslladar la responsabilitat sanitària dels municipis als serveis regionals de benestar (wellbeing service counties o WBSC), alterant així les fronteres lingüístiques establertes. Tradicionalment, els municipis havien garantit la prestació de serveis tant en finès com en suec a les zones bilingües. Després de la reforma, els parlants de suec que constituïen una majoria o una minoria important dins d’un municipi han passat a ser una petita minoria dins de WBSC més grans, alguns dels quals inclouen àrees unilingües sense experiència en la prestació de serveis bilingües. L’anàlisi de dades provinents d’enquestes indica que els parlants de suec dels municipis de majoria suecoparlant són els més satisfets amb els serveis lingüístics, mentre que els de les àrees on són minoria es mostren significativament menys satisfets. Tanmateix, la satisfacció entre els parlants de suec a les àrees on són majoria ha disminuït notablement des de la reforma. L’estudi destaca els reptes que suposa mantenir els drets lingüístics dins d’un sistema de salut universal enmig de canvis estructurals i posa èmfasi en la importància d’atendre les necessitats lingüístiques en un estat amb dues llengües nacionals. , Este estudio analiza el impacto de la reforma social y sanitaria en los servicios sociales y de salud basados en la lengua para la población de habla sueca de Finlandia. La reforma trasladó la responsabilidad sanitaria de los municipios a los servicios regionales de bienestar (wellbeing service counties o WBSC), alterando así las fronteras lingüísticas establecidas. Tradicionalmente, los municipios habían garantizado la prestación de servicios tanto en finés como en sueco en las zonas bilingües. Después de la reforma, los hablantes de sueco que constituían una mayoría o una minoría importante dentro de un municipio han pasado a ser una pequeña minoría dentro de WBSC mayores, algunos de los cuales incluyen áreas unilingües sin experiencia en la prestación de servicios bilingües. El análisis de datos provenientes de encuestas indica que los hablantes de sueco de los municipios de mayoría suecohablante son los más satisfechos con los servicios lingüísticos, mientras que los de las áreas donde son minoría se muestran significativamente menos satisfechos. Sin embargo, la satisfacción entre los hablantes de sueco en las áreas donde son mayoría ha disminuido notablemente desde la reforma. El estudio destaca los retos que supone mantener los derechos lingüísticos dentro de un sistema de salud universal en medio de cambios estructurales y pone énfasis en la importancia de atender a las necesidades lingüísticas en un estado con dos lenguas nacionales.

Bilingualism in the health system: The Catalan case - Ibáñez Ferreté, Òscar-Adrià; Mestres i Farré, Neus (Linguistic Minorities and Society, 2021)
Catalan-speaking citizens living in Catalonia have full, formal rights to use their language with all of their region’s administrations. Nevertheless, the available information on the knowledge and use of Catalan by civil servants shows that health care is a weak spot for regional administrations, due to the difficulty in covering all medical specialties. Plataforma per la Llengua has undertaken research in the form of a survey with a sample of 1,600 Catalan inhabitants, to ascertain the level of satisfaction with the enforcement of linguistic rights in public health and determine the scope of a potential language promotion policy that would have health care staff initiate conversations in Catalan. Results of government surveys suggest that language use (by both patients and providers) in the health care system, compared with language use in other areas of public administration, demonstrates the limits of the current regional language promotion policies in Catalonia. Keywords: catalan, linguistic minorities, linguistic rights, health and social services, language competencies

Tensions linguistiques au Nouveau-Brunswick : attitudes à l’égard du bilinguisme dans le système de santé. - Landry, Michelle; Legault-Leclair, Jacob; McLaughlin, Gilbert (Minorités linguistiques et société, 2024)
Dans cet article, nous examinons les opinions des anglophones à l’égard du bilinguisme dans le système de santé. Les données proviennent d’un sondage mené par la firme Léger du 16 au 24 février 2021. Nous avons mesuré l’effet d’une série de variables sociodémographiques, de l’orientation politique et de l’accord avec un énoncé selon lequel les francophones constitueraient un groupe privilégié sur le fait d’être d’avis que les services bilingues sont suffisamment développés dans le secteur de la santé. En conclusion, les résultats indiquent que les électeurs des partis politiques conservateurs et du People’s Alliance ont en majorité tendance à estimer que le bilinguisme en santé est suffisamment développé. Les variables sociodémographiques et le fait d’affirmer que les francophones représentent un groupe privilégié ne sont pas des variables discriminantes dans notre analyse. Mots-clés : Bilinguisme, Nouveau-Brunswick, système de santé, Acadie, services en français

Loi sur les langues officielles et vitalité des minorités : mission impossible ou oeuvre inachevée ? - Landry, Rodrigue (Minorités linguistiques et société, 2021)
Notre article vise à déterminer les conditions nécessaires pour qu’une loi et des politiques linguistiques puissent avoir un effet réel sur la vitalité d’une minorité. L’article comprend trois parties. Premièrement, nous concluons que la Loi sur les langues officielles (LLO) a eu peu d’effet sur la vitalité des minorités de langue officielle. En deuxième partie, nous distinguons trois acteurs essentiels qui agissent sur la vitalité linguistique : la communauté d’intimité, la société civile de la minorité et l’État. De ces analyses, nous dégageons deux principes sociolinguistiques que toute législation linguistique devrait respecter si son objet est de favoriser la vitalité/revitalisation d’une minorité. Enfin, nous focalisons sur la partie VII de la LLO, la plus susceptible de favoriser la mise en oeuvre d’un aménagement linguistique planifié et global capable de respecter les deux principes sociolinguistiques, de coordonner une synergie d’action des acteurs essentiels et d’avoir un effet réel sur la vitalité des minorités. Mots-clés : Loi sur les langues officielles, vitalité ethnolinguistique, autonomie culturelle, aménagement linguistique, politiques linguistiques, droits linguistiques

Operationalising linguistic unease for the evaluation of language policies in healthcare - Marinaro, Nicole (Revista de Llengua i Dret, 2025)
This contribution presents an original methodological tool for the systematic evaluation of the relevance and comprehensiveness of healthcare language policy design. In particular, the focus of the analysis are public policies that address communication barriers experienced by patients who speak autochthonous or allochthonous languages other than the majority language in their interaction with the healthcare system. Such communication barriers are here conceptualised as “linguistic unease”. Within the epistemological framework of public policy analysis, the tool presented in the article hinges on the operationalisation of the concept of linguistic unease and is hence built on the centrality of the consideration of speakers’ needs. After outlining instances of linguistic unease in healthcare, the article presents the tool in detail and illustrates its employment through a brief practical example. , Aquest article presenta una eina metodològica original per a l’avaluació sistemàtica de la rellevància i l’exhaustivitat del disseny de polítiques lingüístiques en l’atenció sanitària. En concret, l’anàlisi se centra en les polítiques públiques que aborden les barreres de comunicació que experimenten els pacients que parlen llengües autòctones o al·lòctones diferents de la llengua majoritària a l’hora d’interactuar amb el sistema de salut. Aquestes barreres comunicatives es conceptualitzen com a “incomoditat lingüística”. Dins del marc epistemològic de l’anàlisi de les polítiques públiques, l’eina presentada a l’article es basa en l’operacionalització del concepte d’incomoditat lingüística i, com a tal, s’articula al voltant de la centralitat de les necessitats dels parlants. Després d’exposar diversos casos d’incomoditat lingüística en l’atenció sanitària, l’article descriu l’eina en detall i n’il·lustra l’ús a través d’un breu exemple pràctic. , Este artículo presenta una herramienta metodológica original para la evaluación sistemática de la relevancia y la exhaustividad del diseño de políticas lingüísticas en la atención sanitaria. En concreto, el análisis se centra en las políticas públicas que abordan las barreras de comunicación que experimentan los pacientes que hablan lenguas autóctonas o alóctonas diferentes de la lengua mayoritaria en sus interacciones con el sistema de salud. Estas barreras comunicativas se conceptualizan como “incomodidad lingüística”. Dentro del marco epistemológico del análisis de las políticas públicas, la herramienta presentada en el artículo se basa en la operacionalización del concepto de “incomodidad lingüística” y, como tal, se articula en torno a la centralidad de las necesidades de los hablantes. Después de exponer varios casos de incomodidad lingüística en la atención sanitaria, el artículo describe la herramienta en detalle e ilustra su uso a través de un breve ejemplo práctico.

The Basque paradigm shift: From legislative language policies to person-centred care - Montes Lasarte, Aitor; Arauzo, Xabier; Zarate Sesma, Jon (Linguistic Minorities and Society, 2021)
The Basque Country has two official languages, Basque and Spanish, the first being spoken by 37% of the population. The Basque Health Service has developed language schemes to fulfill the legal requirements. Currently, there is a vast transformational shift from legislative policies to an evidence-based, patient-centred care approach. This paper discusses three key issues which could enhance language appropriate care: the recording of patient’s preferred language; the Basque language care pathways as a suitable and effective approach for determining the language of service along the continuum of care; and bilingual electronic medical records, which bring to the fore the challenge of language barriers among professionals. Considering its bilingual human resources, it offers an opportunity for establishing compelling evidence about implementation. Keywords: patient-centred care, bilingual pathways, language appropriate care, preferred language, active offer

Problèmes d’accès aux services en français ? Contactez-nous. Nous pouvons vous aider [infographie] - Ombudsman de l'Ontario (2022)

Problems accessing services in French? Contact us. We can help [infographie] - Ontario Ombudsman (2022)

Situation des populations de langue anglaise au Québec et de langue française au Canada hors Québec : résultats de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
Le présent rapport et l’Enquête sur la population de langue officielle en situation minoritaire de 2022 ont bénéficié du soutien financier et de la collaboration soutenue du ministère du Patrimoine canadien. Cette étude a pu être réalisée grâce au travail de longue haleine de plusieurs équipes et personnes qui se sont relayées au fil des ans pour planifier, concevoir, préparer, tester, réaliser, assurer la qualité des données, documenter, analyser et diffuser cette enquête d’envergure. Les auteurs tiennent à remercier toutes les personnes qui ont participé à ce processus, en particulier, Marie Desnoyers, Éric Caron Malenfant, Daniel Pereira, Claude Girard, Marie‑ Hélène Toupin, Danielle Léger et Catherine Dufour. Plusieurs autres membres du personnel actuel ou passé de Statistique Canada ont contribué de manière importante à cette enquête au fil du temps, dont Siramane Coulibaly, Catherine Frigon, Julien Acaffou, Paul Brisson, Sara Tello, Jean‑Pierre Corbeil, Émilie Lavoie, Deniz Do, Jean‑François Nault, Guylaine Dubreuil, Isabelle Lévesque, Daphné Allard Gervais, Geneviève Caron, Geanina Popescu et Dominique Pérusse, de même que les équipes internes des activités de collecte et de traitement des données. Pour leur soutien, leurs conseils et leur aide à la production du rapport, merci à Laurent Martel, Daphne Fernandes, Juliane Oliveira Pisani Martini et Pierre‑France Bondesen‑David. Soulignons également l’expertise et l’orientation fournies par les réviseurs ainsi que les membres du comité de direction et les membres du comité scientifique de l’enquête.

Situation of English-speaking populations in Quebec and French-speaking populations in Canada outside Quebec: Results of the 2022 Survey on the Official Language Minority Population - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
This report and the 2022 Survey on the Official Language Minority Population received funding and ongoing support from the Department of Canadian Heritage. This study was made possible thanks to the tireless efforts of many different teams and individuals who, over the years, contributed to planning, designing, preparing, testing, conducting, ensuring data quality, documenting, analyzing and publishing this major survey. The authors would like to thank each and every one of them, especially, Marie Desnoyers, Éric Caron Malenfant, Daniel Pereira, Claude Girard, Marie‑Hélène Toupin, Danielle Léger and Catherine Dufour. Many other current or former Statistics Canada staff members have made, over the years, important contributions to this survey including Siramane Coulibaly, Catherine Frigon, Julien Acaffou, Paul Brisson, Sara Tello, Jean Pierre Corbeil, Émilie Lavoie, Deniz Do, Jean‑François Nault, Guylaine Dubreuil, Isabelle Lévesque, Daphné Allard Gervais, Geneviève Caron, Geanina Popescu and Dominique Pérusse, as well as the in‑house data collection and processing teams. For their support, advice and help in producing the report, thanks to Laurent Martel, Daphne Fernandes, Juliane Oliveira Pisani Martini and Pierre‑France Bondesen‑David. We would also like to acknowledge the expertise and guidance of the editors, as well as the members of the Interdepartmental Steering Committee and the survey Scientific Committee.

Approach to the status and management of languages in the catalan public health care system - Pere Mas, Jordi (Linguistic Minorities and Society, 2021)
This article deals with the situation of languages in healthcare in Catalonia. It reports on the measures being carried out by the Ministry of Health of the Government of Catalonia to guarantee that the population may be attended to in their own official language, whether Catalan, Spanish or Occitan, and specifically to promote knowledge and use of Catalan among professionals working in the health system. It provides data on the migratory flows of doctors and nurses and sociolinguistic data. Other sections deal with healthcare services provided in non-official languages and in Catalan sign language, as well as language-related complaints and the measures implemented to make Catalan a suitable and prestigious language for medical and scientific communication. It concludes by listing the challenges that still need to be tackled to give Catalan greater presence and to raise its status in the field of health. Keywords: healthcare, health, Catalan, linguistic planning, healthcare professionals, official languages, Catalonia

Quebec’s English-speaking community and the partnership approach of its networks in health - Pocock, Joanne (Linguistic Minorities and Society, 2021)
This article discusses the networking and partnership approach of improving access to public health and social services, with an interest in informing best practices for official language populations in a minority context. The case of Canada’s official language minority residing in the province of Quebec and its Community Health and Social Services Network (CHSSN) is explored. Elements that support or inhibit partnership functioning, including innovative community-based participatory evaluation (CBPE) techniques, are explored. The contribution of the approach in improving the situation of Quebec’s minority language communities with respect to their health care access is highlighted. Keywords: official language minority communities, intersectoral partnerships, access to public health care, language policy, community-based participatory evaluation (CBPE)

Navigating the meso-level bottleneck: Language rights implementation in Welsh healthcare - Prys, Cynog; Hodges, Rhian (Revista de Llengua i Dret, 2025)
Language is a key factor in the delivery of effective healthcare, especially in settings where service users speak a minoritised language. In Wales, the Welsh Government has acknowledged the importance of linguistic inclusion through initiatives such as the More than just words strategy, which aims to embed the Welsh language into health and social care services. The introduction of The Welsh Language Standards (No. 7) Regulations in 2018 marked a significant statutory development, placing legal obligations on health boards to provide services in Welsh. Despite these policy-level advancements, the integration of Welsh language services within healthcare remains uneven. Reports have highlighted persistent gaps and inconsistencies in Welsh language service provision, raising concerns about the practical challenges of implementation and its impact on service users. In this paper, we examine the structural and operational barriers encountered by meso-level actors – particularly local health boards – responsible for implementing national language policy in everyday service delivery. Although the analysis is situated in the Welsh context, the paper contributes to a broader understanding of the administrative bottlenecks that can arise when implementing public services in a minoritised language context. It highlights the need to critically examine the institutional dynamics that shape the translation of policy into practice and the implications for minoritised languages such as Welsh. , La llengua és un element clau en la prestació d’una atenció sanitària de qualitat, sobretot en contextos en què els usuaris parlen una llengua minoritzada. A Gal·les, el Govern gal·lès ha reconegut la importància de la inclusió lingüística a través d’iniciatives com ara l’estratègia More than just words, que té l’objectiu d’integrar la llengua gal·lesa als serveis de salut i d’assistència social. L’any 2018, la introducció del Reglament núm. 7 sobre la llengua gal·lesa va marcar un avenç normatiu important, ja que va imposar obligacions legals d’oferir serveis en gal·lès als consells de salut. Malgrat aquests avenços a nivell polític, la incorporació de serveis en llengua gal·lesa en l’atenció sanitària continua sent desigual. Alguns informes han posat de manifest l’existència de buits continuats i d’incoherències en la prestació de serveis en gal·lès, cosa que ha suscitat interrogants sobre els reptes pràctics de la seva implementació i l’impacte que té en els usuaris. En aquest article s’analitzen les barreres estructurals i operatives que es troben els agents situats al nivell meso –en concret els consells de salut locals– responsables d’implementar les polítiques lingüístiques nacionals en l’atenció diària. Malgrat que l’anàlisi se situa en el context gal·lès, l’article aporta una visió més àmplia dels colls d’ampolla administratius que poden sorgir a l’hora d’implementar serveis públics en un context de llengües minoritzades. També destaca la necessitat d’analitzar críticament les dinàmiques institucionals que modulen la traducció de les polítiques a la pràctica i les implicacions per a llengües minoritzades com ara el gal·lès. , La lengua es un elemento clave en la prestación de una atención sanitaria de calidad, sobre todo en contextos en que los usuarios hablan una lengua minorizada. En Gales, el Gobierno galés ha reconocido la importancia de la inclusión lingüística a través de iniciativas como la estrategia More than just words, que tiene el objetivo de integrar la lengua galesa en los servicios de salud y de asistencia social. En 2018, la introducción del Reglamento núm. 7 sobre la lengua galesa marcó un avance normativo importante, ya que impuso obligaciones legales de ofrecer servicios en galés en los consejos de salud. A pesar de estos avances a nivel político, la incorporación de servicios en lengua galesa en la atención sanitaria sigue siendo desigual. Algunos informes han puesto de manifiesto la existencia de vacíos continuados e incoherencias en la prestación de servicios en galés, lo que ha suscitado interrogantes sobre los retos prácticos de su implementación y el impacto que tiene en los usuarios. En este artículo se analizan las barreras estructurales y operativas que encuentran los agentes situados al nivel meso –en concreto los consejos de salud locales– responsables de implementar las políticas lingüísticas nacionales en la atención diaria. Aunque el análisis se sitúa en el contexto galés, el artículo aporta una visión más amplia de los cuellos de botella administrativos que pueden surgir a la hora de implementar servicios públicos en un contexto de lenguas minorizadas. También destaca la necesidad de analizar críticamente las dinámicas institucionales que modulan la traducción de las políticas a la práctica y las implicaciones para lenguas minorizadas como el galés.

Rhetoric and reality: A critical review of language policy and legislation governing official minority language use in health and social care in Wales - Prys, Cynog; Hodges, Rhian; Roberts, Gwerfyl Wyn (Linguistic Minorities and Society, 2021)
A concerted attempt is being made by the Welsh Government to revitalize the Welsh language in Wales through language legislation and policy initiatives. This paper explores the political rhetoric and practical reality of these recent legislative developments, as they pertain to the health care sector. It offers a qualitative analysis of written evidence provided by key stakeholders during the consultation process on the new legally-binding requirements of Welsh Language Standards for health care providers in Wales. We argue that these meso-level service providers are critical linchpins within the health care system and that it is at the meso level that full tensions between the macro rhetoric and micro reality occur. This contribution highlights shortcomings and barriers to Welsh language service provision in health care in Wales and recommends the adoption of wide-ranging, holistic approaches to language planning that meet the language needs of patients outlined by the Welsh Government. Keywords: health and social care, language planning, minority language, Welsh, Wales

Mémoire sur la santé numérique en français en Ontario. Examen des documents d'orientation stratégique - Réseau des services de santé en français de l'Est de l'Ontario (2021)

Je suis insatisfait(e) des services de santé reçus. Que faire ? Comment procéder ? [infographie] - Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada; Société Santé en français (2022)

Access to health and social services for Quebec’s English-Speaking Minority Communities: Recent challenges, legislative context, and research recommendations. - Shoumarova, Lina (Quebec English-Speaking Communities Research Network, 2024)

Pour une réforme de la santé respectueuse des deux communautés linguistiques officielles. Mémoire présenté à l’honorable Dorothy Shephard, ministre de la Santé, dans le cadre de la consultation publique sur l’avenir des soins de santé dans la province du Nouveau-Brunswick - Société de l'Acadie du Nouveau-Brunswick (2021)

Improving access to health services in French: The power of networking and knowledge mobilization, a proven Canadian Model - Tremblay, Michel; Leis, Anne (Linguistic Minorities and Society, 2021)
Language barriers have a detrimental impact on access to health services and compromise patients’ safety. The purpose of this article is to describe and evaluate how the Société Santé en français (SSF) and the 16 French Language Health (FLH) networks used networking and knowledge mobilization for improving access to health services in French for Francophone and Acadian minority communities (FAMC). Method: Data was extracted from the 2013-2018 program’s reports and evaluation. Results confirmed that networking effectively mobilized key partners for better access to health services in French regardless of location. This access increased incrementally as a function of the customized level of support provided to the system by the SSF and the FLH networks and, to a lesser extent, when FAMC represented over 3.5% of the total population in the region, province or territory. Networking and knowledge mobilization contribute to augmenting access to safe, quality health services in French for FAMC. Keywords: access, partnership and networking, active offer, language barriers, knowledge mobilization